Author Response: Evaluation of Efficacy and Tolerability of First-Line Therapies in NMOSD. (9th February 2021) - Zephir, Helene; Poupart, Julien; Deschamps, Romain; Audoin, Bertrand; Ciron, Jonathan; Maillart, Elisabeth; Papeix, Caroline; Collongues, Nicolas; Bourre, Bertrand; Cohen, Mickaël; Wiertlewski, Sandrine; Outteryck, Olivier; et al.
Abstract : We thank Maria Isabel Leite for her comments on our article. 1